2022
DOI: 10.3389/fgene.2022.829283
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-10 Polymorphism (rs1800896, rs1800871, and rs1800872) With Breast Cancer Risk: An Updated Meta-Analysis Based on Different Ethnic Groups

Abstract: Background: The interleukin10 (IL-10) gene polymorphisms have been indicated to be associated with breast cancer (BC) risk, but the findings are still controversial. To derive a more precise evaluation, we performed a comprehensive meta-analysis.Methods: A systematic literature search was conducted using PubMed, Embase, CNKI, China biomedical (CBM), and Google Scholar to 29 March 2020. Revman5.3 and Stata 12.0 software analyzed the data, and the strength of the association was identified using the odds ratio (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Consistent with our MR analysis findings, multiple meta-analyses and observational studies have demonstrated a robust association between the inflammatory cytokines IL-5 and IL-16, and the susceptibility to breast cancer [ 12 14 ]. Previous experimental studies have suggested that IL-5 and IL-16 exhibit significant pro-inflammatory activity.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with our MR analysis findings, multiple meta-analyses and observational studies have demonstrated a robust association between the inflammatory cytokines IL-5 and IL-16, and the susceptibility to breast cancer [ 12 14 ]. Previous experimental studies have suggested that IL-5 and IL-16 exhibit significant pro-inflammatory activity.…”
Section: Discussionsupporting
confidence: 89%
“…and the susceptibility to breast cancer [12][13][14]. Previous experimental studies have suggested that IL-5 and IL-16 exhibit significant pro-inflammatory activity.…”
Section: Plos Onementioning
confidence: 99%
“…A meta-analysis published in 2021 confirmed the association between the rs1800872 variant and the risk of cervical cancer [ 18 ]. Several other meta-analyses have shown the association between this variant and the risk of breast cancer [ 19 , 20 ]. Our study found a trend toward a lower occurrence in NET patients compared to that in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 is an important inflammatory factor, and many studies show that inflammation in the tumor microenvironment plays an important role in the progression of breast cancer [ 14 ]. IL-10 plays an important role in the pathogenesis of cancer: the excessive production of IL-10 increases the likelihood of tumors due to immunosuppression [ 6 , 15 , 16 , 17 ]. Elevated levels of IL-18 in the serum of patients with various forms of cancer correlate with the progression of the disease and the development of metastasis.…”
Section: Introductionmentioning
confidence: 99%